2008
DOI: 10.1158/0008-5472.can-08-0484
|View full text |Cite
|
Sign up to set email alerts
|

Single-Molecule PCR Analysis of Germ Line Mutation Induction by Anticancer Drugs in Mice

Abstract: Understanding and estimating the genetic hazards of exposure to chemical mutagens and anticancer drugs in humans requires the development of efficient systems for monitoring germ line mutation. The suitability of a single-molecule PCRbased approach for monitoring mutation induction at the mouse expanded simple tandem repeat (ESTR) locus Ms6-hm by chemical mutagens and anticancer drugs has been validated. The frequency of ESTR mutation was evaluated in the germ line of male mice exposed to the well-characterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
39
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 44 publications
1
39
0
Order By: Relevance
“…We previously showed that a single dose as low as 40 mg/kg can increase mutation frequency at the Ms6hm ESTR locus in the germ line of directly exposed male mice (15). Single doses for anticancer treatment in humans are typically between 400 and 1,200 mg/m 2 (16); the equivalent mouse dose is 130-400 mg/kg.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously showed that a single dose as low as 40 mg/kg can increase mutation frequency at the Ms6hm ESTR locus in the germ line of directly exposed male mice (15). Single doses for anticancer treatment in humans are typically between 400 and 1,200 mg/m 2 (16); the equivalent mouse dose is 130-400 mg/kg.…”
Section: Resultsmentioning
confidence: 99%
“…After metabolic activation, MMC forms a number of sequence-specific DNA adducts, including alkylated monoadducts and cross-linked adducts (17). Single doses of 2.5 or 5 mg/kg lead to dose-dependent statistically significant increases in ESTR mutation frequency in the germ line of directly exposed male mice (15). Single doses in humans are typically between 10 and 20 mg/ m 2 (16), with equivalent mouse doses of 3-6 mg/kg.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A nonlinear relationship between dose and ESTR mutation frequencies has been reported in the germ line of male mice exposed to DNA damaging agents (19,20). A decrease in mutation frequency with increasing dose may be the consequence of increased cytotoxicity, with the higher dose inducing higher rates of cell death precluding the recovery of mutated cells (17,21).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that paternal exposures to chemical mutagens (20), ionizing radiation (38,39), and particulate air pollution (40) increase ESTR mutation frequencies in sperm, and, more importantly, induce persistent genomic instability in the F1 and F2 offspring of exposed mice (32,38,41). Although not directly assessed in the present study, the observation that the mutated alleles are already present in the sperm of exposed mice at frequencies that match those observed in their offspring (16,20) lends support to the notion that the tobacco smokeinduced germ-line mutations reported here would be passed on to the next generation. The impact of these mutations on the health of the offspring remains uncertain, as the evidence linking increased mutation rates in noncoding tandem repeat regions to a phenotypic effect or to increased mutations rates in proteincoding regions is not well established.…”
Section: Resultsmentioning
confidence: 99%